Developmental bibliotherapy in the context of needs of contemporary child - Marković, Ana S (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2015)
This paper provides a short outline of the bibliotherapy process and considers some of the main techniques used in its implementation. The paper underlines and investigates the difference between clinical and developmental bibliotherapy, in addition to providing a brief overview of this psychotherapeutical discipline. The author also cites several definitions of the term bibliotherapy and draws the conclusion that they all have the same defining feature, that is the use of books to help people. Some of the chapters of the paper deal with topics such as bibliotherapy and children’s need, bibliotherapeutical process, skills and characteristics of a good bibliotherapist and the limitations of bibliotherapy.